Study on deformation mechanism and control technology of surrounding rock during reuse of gob side entry retaining by roof pre-splitting. (July 2022) - He, Fulian; Xu, Xuhui; Qin, Binbin; Li, Liang; Lv, Kai; Li, Xiaobin
Highlights: The deformation mechanism of surrounding rock was revealed during reuse of gob side entry retaining. The relationship between roadway support system and surrounding rock state was determined. A distinctive combined support technology for roadway was proposed. Abstract: In this study, we aiming at the problems of severe surrounding rock deformation and support failure during the reuse of gob side entry retaining, we conducted field observations, theoretical analyses, numerical simulations and engineering projects to analyze the surrounding rock deformation mechanism, and we proposed a corresponding combined support technology. The results show that: (1) the surrounding rock failure is mainly affected by the advance abutment pressure, followed by the lateral abutment pressure, and the lateral abutment pressure has a certain lag. (2) According to borehole detection and theoretical analyses, multiple dynamic pressures influence the relationship between roadway support system and surrounding rock state. (3) The high proportion of inelastic zone volume is the main cause of severe surrounding rock deformation. Consequently, we developed a combined support technology, and applied it to an engineering project, realizing roadway stability; thus, the study provides a reference for similar engineering projects.